SINAPIC ACID ATTENUATES 7,12-DIMETHYLBENZ[A] ANTHRACENE-INDUCED ORAL CARCINOGENESIS BY IMPROVING THE APOPTOTIC ASSOCIATED GENE EXPRESSION IN HAMSTERS - J, KALAIMATHI; K, SURESH (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: The main objective of the present study is to examine the histological changes and apoptotic associated gene expression during 7,12-dimethylbenz[a] anthracene (DMBA)-induced buccal pouch carcinogenesis in male golden Syrian hamsters. Methods: Squamous cell carcinoma was induced in the buccal pouch of male Syrian golden hamsters by painting with 0.5% solution of DMBA in liquid paraffin 3 times per week for 16 weeks to induce the development of oral tumors. Sinapic acid (50 mg/kg b.wt) were either applied topically to the oral tumor lesions or administrated orally at varying dosage to hamster animals with oral tumor for 14 weeks. The experiment was terminated at the end of 16 weeks. The development of oral carcinogenesis was confirmed by the histopathological analysis and expressions of apoptotic associated genes were analyzed by the immunohistochemical methods. th Results: We observed altered status of apoptotic associated gene expression (P53, B-cell lymphoma [Bcl-2], Bax, and caspase-3) was observed in the DMBA alone painted hamsters as compared to control hamsters. Oral administration of sinapic acid improved the histological changes and significantly stimulate the apoptotic associated genes expression, especially caspase-3 but decreasing Bcl-2 protein production. Conclusion: It can be evident from the findings of this research work concluded that oral administration of sinapic acid are effective at inhibiting tumor cell proliferation and stimulating apoptosis in oral cancer suggesting that sinapic acid have chemopreventive effects on DMBA-induced experimental oral carcinogenesis. Keywords: Apoptosis, 7,12-dimethylbenz[a] anthracene, Hamster, Histology, Sinapic acid.